Practical design of masonry structures proceedings of a symposium organized by the Institution of Civil Engineers and co-sponsored by the Institution of Structural Engineers and held in London on 23-24 September 1986. (Thomas Telford, 1987)
This volume deals with the practical design of masonry structures. Topics covered in the book include brick column construction for commercial buildings, the use of pre-stressed concrete lintels in composite lintel construction and the compressive strength of masonry walls built laid flat.